ANALISIS PENGARUH PENDIDIKAN DAN KEMAMPUAN KERJA TERHADAP PENGAWASAN DAN PRESTASI KERJA PEGAWAI BADAN PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASSET DAERAH (BPPKAD) KABUPATEN SUMENEP - Lukmanul Hakim; Woro Utari (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
The aim of this study is to analyze the effect of education and work ability on supervision and work performance of employees at the Regional Financial and Asset Management Revenue Agency (BPPKAD) Sumenep Regency. The type of research is explanatory research, the approach used is a quantitative approach with a total sample of 86 employees. The results showed that education and work ability partialy had a significant effect on supervision and employee performance at the Regional Revenue, Financial and Asset Management Agency (BPPKAD) of Sumenep Regency.